2012
DOI: 10.1089/cbr.2011.1158
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Therapeutic Efficacy of Rhenium-188 Radiolabeled-Liposome and 5-Fluorouracil in LS-174T Human Colon Carcinoma Solid Tumor Xenografts

Abstract: Nanoliposomes are important carriers capable of packaging drugs for various delivery applications. Rhenium-188-radiolabeled liposome ((188)Re-liposome) has potential for radiotherapy and diagnostic imaging. To evaluate the targeting of (188)Re-liposome, biodistribution, microSPECT/CT, whole-body autoradiography (WBAR), and pharmacokinetics were performed in LS-174T human tumor-bearing mice. The comparative therapeutic efficacy of (188)Re-liposome and 5-fluorouracil (5-FU) was assessed according to inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…13 Re-liposome has a comparative therapeutic efficacy with chemotherapeutic drug 5-FU in colon carcinoma ascites, we found that 188 Re-liposome possesses a better therapeutic efficacy in both lung-metastatic and solid-tumor animal models. 18,[20][21][22] No documents using 188…”
Section: Introductionmentioning
confidence: 99%
“…13 Re-liposome has a comparative therapeutic efficacy with chemotherapeutic drug 5-FU in colon carcinoma ascites, we found that 188 Re-liposome possesses a better therapeutic efficacy in both lung-metastatic and solid-tumor animal models. 18,[20][21][22] No documents using 188…”
Section: Introductionmentioning
confidence: 99%
“…23,33,35,54,71 The radionuclide after-loading method has provided higher labeling efficiencies (>90%) and the greatest in vivo stability for 99m Tc, 111 In and 67 Ga radionuclides for nuclear imaging 23,24,27,35,59,[84][85][86] as well as 186 Re and 188 Re radionuclides for radiotherapy. 72,[87][88][89][90][91][92] This kind of approach is also useful in preparing polymeric NP, lutetium-177-loaded poly(D,L-lactide-co-glycolide) (PLGA) NPs are formulated by simply incubation of pre-formulated blank PLGA 50:50 or 75:25 NPs by incubating with 177 Lu-DOTA-Tyr 3 -octreotate (DOTATATE), although the percentage of encapsulation was about 77%. 93 In the second approach, the radionuclides are bounded to a lipid chelator, inserted and loaded into the liposomal bilayer or radionuclide chelators are covalently attached to the surface of the liposomes or NPs after forming.…”
Section: Nanopreparations For Nuclear Imaging and Ratherapymentioning
confidence: 99%
“…111 The SPECT/CT imaging of 188 Re-liposome targeting on LS-174T human colorectal tumor bearing nude mouse model were also proved recently. 89 SPECT/CT imaging of passive tumor targeting, pharmacokinetics and excretion of 188 Re-liposomes were studied in C26 murine colon carcinoma solid tumor-bearing mice, C26 colon carcinoma ascites-bearing mice, C26 colon carcinoma lung metastatic mice model and LS-174T human colon carcinoma solid tumor-bearing mice. Elimination half-lives (T 1/2λz ) of of PEGylated nanoliposome therapeutics loaded with 188 Re.…”
Section: Nuclear Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…[93][94][95] Rhenium-188 ((188)Re) labeled PEGylated liposomes carrying anticancer drugs showed the potential benefits of tumor specific drug accumulation and cancer growth inhibition. [96][97][98][99] PEGylated liposomes encapsulating (111)Re and vinorelbine was as effective as PEG liposomal (188)Re and doxorubicin for radiochemotherapy of CRC models.…”
Section: Liposomal Formulated Photosensitizers and Radiochemotherapeumentioning
confidence: 99%